Tutoring Service provided by Teachers in the New Secondary School in Peru (Praxis Educativa, 2021)
The objective of the study was to identify the level of knowledge that teachers have about the tutoring service in the new secondary school in C.E.S. “San Juan Bosco” Puno 20. Research with a quantitative, descriptive field approach, non-experimental and cross-sectional design, with a population of 30 professors who work at the C.E.S. "San Juan Bosco" Puno, on the tutoring service in the new high school. The sample was intentional non-probabilistic. The techniques used were the survey and knowledge test. It concludes that teachers, if they have knowledge about tutoring, require new alternatives of formal training to strengthen the service of the guidance action.
Keywords: training; orientation; teacher; secondary school; tutoring